The Essential Role of Elementary School Teachers in Guidance and Counseling Services: Developing Student Empathy in Indonesia in Support of SDG 4 - Firdian Setiya Arinata; Awalya Awalya; Eem Munawaroh; Ashari Mahfud; Najma Sana Nadhirah Hilman; Adinuringtyas Herfi Rahmawati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: Empathy is a fundamental social-emotional competency that supports students’ personal development, positive interpersonal relationships, and inclusive learning environments. However, increasing cases of bullying, intolerance, and interpersonal conflicts among elementary school students indicate that empathy development remains a significant educational challenge in Indonesia. This study aims to examine the essential role of elementary school teachers in implementing guidance and counseling services to foster students' empathy while contributing to Sustainable Development Goal (SDG) 4, particularly the promotion of quality and inclusive education. Method: A Systematic Literature Review (SLR) using the Arksey and O'Malley scoping review framework. Relevant studies published between 2014 and 2024 were identified through Garuda, Taylor & Francis, Open Knowledge Maps, and PubMed databases. Literature selection followed predetermined inclusion and exclusion criteria, while thematic analysis was conducted to synthesize evidence regarding teachers' roles and effective strategies for empathy development through guidance and counseling services. Results: The findings demonstrate that elementary school teachers play a pivotal role in integrating guidance and counseling into daily learning activities to enhance students' empathy. Effective strategies include experiential learning-based guidance programs, strengthening teacher–student relationships, collaboration with parents, bullying prevention initiatives, violence prevention education, and cognitive empathy enhancement. These approaches contribute to students' social-emotional development, reduce aggressive behavior, and support the creation of safe and inclusive school environments aligned with SDG 4. Novelty: Unlike previous studies that primarily focused on either teacher roles or empathy interventions separately, this review integrates current evidence to provide a comprehensive synthesis of elementary school teachers' guidance and counseling practices for empathy development within the Indonesian educational context. Furthermore, the study explicitly connects empathy-based guidance and counseling with the achievement of SDG 4 (Quality Education), offering practical recommendations for integrating empathy development into elementary education policies and classroom practices.